Efektivitas Media Edukasi Panduan Pertolongan Pertama Keadaan Gawat Darurat terhadap Peningkatan Pengetahuan dan Skill Mahasiswa Keperawatan - Tuti Sahara; Isni Hijriana; Mini Harianti (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
First aid in emergencies is an essential skill that must be possessed by nursing students as prospective health workers. Educational media in the form of practical guidebooks is believed to be able to improve students' knowledge and skills, but their effectiveness needs to be proven empirically. This study aims to determine the effectiveness of the educational media of the Emergency First Aid Guide in improving the knowledge and skills of Basic Life Assistance (BHD) for nursing students. The research design used was pre-experimental with a one group pretest-posttest design approach. The research sample consisted of nursing students selected through purposive sampling techniques. The research instruments include a knowledge questionnaire and a BHD skill observation sheet. Data analysis was carried out by the normality test and the Wilcoxon Signed Rank Test. The results showed a significant improvement in respondents' knowledge from an average of M: 12; SD ± 2.52 to M: 17; SD ± 1.55 (Z = -7.789; p = 0.00), as well as an improvement in BHD skills from M: 83; SD ± 9 to M: 99; SD ± 10.2 (Z = -7.789; p = 0.00). These findings show that educational media in the form of handbooks is effective in improving the ability of nursing students to deal with emergency situations. This media can be used as an alternative strategy in emergency nursing learning to support students' clinical readiness.